PREPARATION, CHARACTERIZATION AND PHOTOELECTROCATALYTIC ACTIVITY OF Cu@N-TiO2/Ti THIN FILM ELECTRODE - MUHAMMAD NURDIN, (International Journal of Pharma and Bio Sciences, 2014)
This research focused on the preparation and characterization of Cu@N-TiO2/Ti (N-TiO2/Ti decorated with Cu) thin film electrode and its activities test in photoelectrocatalytic system. This study investigated the time effect of Copper (Cu) electrodeposition and the concentration of nitrogen (N) in the photocatalytic characteristics of TiO2. The catalyst has been prepared for activities test on congo red. These results indicated the value of the smallest band gap (3.06 eV) on the N-TiO2 prepared by sol - gel method (using 1M urea), thin film electrode of N-TiO2/Ti further decorated with Cu using electrodeposition method with the highest activity was 20 seconds. The thin film electrode of Cu@N-TiO2/Ti showed excellent activity under visible light illumination, which gave the best photocurrent and capable to degrade congo red better than TiO2/Ti (12.11%) or N-TiO2/Ti (34.87%) which was equal to 49.38%. This electrode might be recommended for Chemical Oxygen Demand Sensor.